Psychological pressure and the right to determine the moves in dynamic tournaments: Evidence from a natural field experiment - Mark Kassis; Sascha Leonard Schmidt; Dominik Schreyer; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2020)
In this paper, we show that the right to determine the sequence of moves in a dynamic team tournament improves the chances of winning the contest. Because studying dynamic team tournaments - like R&D races - with interim feedback is difficult with company data, we examine decisions of highly paid professionals in soccer penalty shootouts and show that teams whose captains can decide about the shooting sequence are more likely to win the shootout. So, managerial decisions matter for outcomes of dynamic tournaments and we discuss potential reasons for this finding.
Keywords: C93; D00; D81; D91; Z20; 330; Dynamic tournament; sports professionals; psychological pressure; value of decision rights; penalty shoot-outs; behavioral economics